Developing Incentives and Capacity for SustainableWaste Reuse in Uganda - Kakembo, Frederick; Nassanga Nakate, Rhodah (My University, 2014)
This paper explores prospects for developing incentives and capacity for sustainable waste reuse in Uganda. Whereas urban authorities focus on waste collection and disposal as a sole approach o waste management, there is lack of sufficient resources to accomplish the task. It was premised that a combination of economic incentives, capacity building and policy reforms could be more effective approach to waste management. The study transcended the traditional approach that seems to conceive solid waste management and wastewater management as separate entities. Data was collected through qualitative and quantitative methods involving: personal interviews, documents analysis, literature reviews, baseline surveys and feasibility studies. Findings suggest that opportunities and prospects for waste reuse include; high organic components in the wastes, rising costs of firewood and charcoal, existence of private waste collectors, existence of umbrella organizations (such as UWASNET) and availability of preliminary IEC materials. The barriers facing the reuse of waste materials include: low technical skills, high start-up/capital investments, socio-cultural sensitivities, non-conducive policy environment and lack of a supportive institutional framework. It is suggested that barriers could partly be reduced through capacity building initiatives, sensitization programmes, userfriendly financing models and development of an institutional framework to bring together key stakeholders.
Keywords: sustainable waste reuse; waste collection and disposal; Uganda